From the lens of the clinical residents: undergraduate to postgraduate medical education and the transition process. Issue 1151 (16th September 2020) - Demiroren, Meral; Atilgan, Burge; Tasdelen Teker, Gulsen; Turan, Sevgi
ABSTRACT: The concept of continuity in medical education reflects the progressive professional and personal development that physicians need in education. The aim of this study is investigating the views of the residents about the adequacy of undergraduate and postgraduate education in the context of preparing them for the next stage and their perceptions about the transition period. This phenomenological study was conducted at Hacettepe University Medical School. The study group consisted of medical and surgical sciences residents in the first year and last year of postgraduate medical education. Four focus group interviews were held with the participation of 21 residents. The participants emphasised that practising with real patients under supervision by taking an active role in healthcare teams was important for their preparation for the next stage in their carrier. However, their educational experiences during undergraduate medical education differed in community-based education, scientific research training, learning in small groups, internship and guidance of clinical educators. The transition period has been expressed with the concepts of identity change, high responsibilities and expectations required by the new identity, adaptation to the healthcare team, institution, and health system, meeting the expectations in an overly busy work environment, and feelings of incompetence. Participants pointed out that curriculum, which was declared and taught, educational environments, assessment approaches, consultancy systems and practices differed between the clinical departments. In line with the principles of competency-based education, practices related to the development and assessment of the competencies with all professional aspects in postgraduate medical education can be strengthened.